Risk Assessment of Feasibility Study for Toll Road X - Y with Public Private Partnership Scheme - Hanie Teki Tjendani; Risma Marleno; Hendry Hendry; Iwan Subiyantoro (U Karst, 2021)
The PPP scheme is carried out in Indonesia to procure public infrastructure but is constrained by the government's limited funds. Risk assessment is very important for investors to do to find out the uncertainty that can occur in investing their funds in infrastructure. This study aims to assess the Risk of Feasibility on the X - Y Toll Road, where the location is part of the East Java Province economic development acceleration program by President Regulation number 80 of 2019. The assessment carried out includes risk analysis in the pre-construction, construction, and post-construction stage. The data used are primary data and secondary data. From the assessment results, it was found that most of the assessment points were categorized as medium risk, and there was a little high risk. Still, this project is very profitable because it will be able to synergize with the previously planned infrastructure. The X-Y toll road is still possible by paying attention to risk factors and complying with risk mitigation efforts. The toll road procurement scheme with Public-Private Partnership (PPP) already has a robust legal rule and has been guaranteed in terms of security, and this scheme is very potential to be implemented.